AIRLINE RESPONSIBILITY TO PASSENGER AIR TRANSPORT DUE TO FORCE MAJEURE REVIEW FROM LAW NUMBER 1 YEAR 2009 CONCERNING FLIGHT (PT. Batik Air Indonesia Banyuwangi Airport Branch) - Rudi Mulyanto (RADJA PUBLIKA, 2021)
The implementation of flights often cannot be done either from the passenger side, or from the airline side. Flight cancellations made by airlines are a form of flight delays. Departure times are delayed, even cancellations without prior notification are very detrimental to passengers because they cannot arrive at their destination according to the expected time. Force majeure is one of the reasons airlines cancel their flight schedules due to bad weather or natural disasters. In the rules, the carrier's obligation is to give full responsibility to passengers, one of which is to ensure timely transportation. all have been regulated in Law Number 1 of 2009 concerning Aviation and its implementation is regulated in the Regulation of the Minister of Transportation.In this study, the author uses empirical research that uses descriptive analysis and a qualitative approach. Sources of data were collected through observation, interviews and documentation. After the data is collected, the data is processed by editing, classifying, and grouping according to the problem formulation. Then, it is reviewed and analyzed by connecting the data and literature review.The conclusions of this study are: 1) The responsibility of the airline company in the event of a flight delay or cancellation of the party acting as the carrier has the responsibility for the loss suffered by the passenger. The form of compensation in the case of flight cancellations can be in the form of a refund or ticket refund, rescheduling, or reroute. 2) Flight cancellations by airlines can cause material and immaterial losses for passengers. Airlines have provided compensation in terms of material losses, namely in the form of ticket refunds or ticket refunds, but in practice there are still shortcomings and are not in accordance with regulations.